A quasi‐linear structure of the southern margin of Eurasia prior to the India‐Asia collision: First paleomagnetic constraints from Upper Cretaceous volcanic rocks near the western syntaxis of Tibet. Issue 7 (21st July 2015) - Yi, Zhiyu; Huang, Baochun; Yang, Liekun; Tang, Xiangde; Yan, Yonggang; Qiao, Qingqing; Zhao, Jie; Chen, Liwei
Abstract: We report the first combined geochronologic and paleomagnetic study of volcanic rocks from the Shiquanhe and Yare Basins at the westernmost Lhasa Terrane, which aims to provide an accurate constraint on the shape and paleoposition of the southern margin of Asia prior to the India‐Asia collision. Three new 40 Ar/ 39 Ar ages of 92.5 ± 2.9 Ma, 92.4 ± 0.9 Ma, and 79.6 ± 0.7 Ma determined by fresh matrix or feldspar from lava flows suggest a Late Cretaceous age for the investigated units. Characteristic remanent magnetizations have been successfully isolated from 38 sites which pass positive fold and/or reversal, conglomerate tests and are hence interpreted as primary in origin. The two paleopoles obtained from Yare and Shiquanhe yield consistent paleolatitudes of 13.6°N ± 9.6°N and 14.2°N ± 2.7°N, respectively (for a reference site of 31.5°N, 80°E), indicating that the southern margin of Asia near the western syntaxis was located far south during the Late Cretaceous time. A reconstruction of the Lhasa Terrane in the frame of Eurasia with paleomagnetic data obtained from its western and eastern parts indicates that the southern margin of Eurasia probably had a quasi‐linear orientation prior to the collision formerly trending approximately 315°E. This is compatible with the shape of the Neo‐Tethys slab observed from seismic tomographic studies. Our findings provide a solid basis for evaluating Cenozoic crustal shortening in the Asian interior and the size of Greater India near the western syntaxis. Key Points: Two late Cretaceous paleopoles are reported from the western Lhasa Terrane The southern margin of Asia near west syntax was located at ~14°N A quasi‐linear southern margin of Eurasia prior to the collision is defined